The Impact of Unwise Mobile Phone Usage on Mental Health and Social Interaction - Yasminar Amaerita Telaumbanua; Pintauli Lase; Masirida Giawa; Citra Kasih Zendrato; Mutiara Putri Zebua (Journal on Education, 2024)
The rapid technology advances in education have a significant impact on students' social interactions and mental health. Mobile phones, especially those used in teaching, provide flexible and accessible learning options, but if unwise can negatively impact social interactions and mental health. Excessive use of mobile phones can increase the risk of loneliness, anxiety and hopelessness among students and can negatively impact mental health, reduce the quality of social interactions and negatively impact academic performance. This study used quantitative methods with questionnaire techniques to collect data involving 32 sixth-semester students of the English Education Study Program. The researchers found the data results showed that most agreed that stress, tension and sleep disturbances were caused by unwise mobile phone use. This highlights the need for better education to address mobile phone misuse and encourages future researchers to find ways to manage mobile phone use wisely among university students.